(untitled) (Research, Society and Development, 2020)
Economies based on non-renewable resources lead, in the long run, to the search for ways to diversify them, since the incentives generated by this industry are limited in time. This study uses the information and knowledge economy as a background to explore whether the production of knowledge at a university in Minas Gerais has the economic potential to diversify the local economy. The objective of the research was to analyze the production of knowledge, in order to know its processes, to investigate whether they generate economic responses capable of meeting the expectations of the three agents involved (University, Companies and Government), through the real productive, social, and economic impact of this Higher Education Institution. For this purpose, the research compares the proposal for a new economic base with the current one, a mining company. The study is of a qualitative nature and uses concepts from Economics and Production Engineering to evaluate the hypotheses proposed by it. Through the analysis of the economic influence that comes from the production of knowledge at the University, it was possible to project its financial and social participation and reach the conclusion that, although the financial impact is not so significant, when compared to the previous activity, the participation in the economy of information and knowledge proves to be relevant and impacts areas of government, business and social interests.